Epstein–Barr virus‐related lymphoma in rheumatoid arthritis: implications for long‐term usage of immunosuppressive drugs and review of the literature. Issue 10 (23rd May 2022) - He, Jianna; Williamson, Luke; Cai, Ken; Wong, Peter; Sturgess, Allan; Taper, John; Manolios, Nicholas
Abstract: Background: Rheumatoid arthritis (RA) is a common autoimmune disease where methotrexate (MTX) is widely used as the first‐line therapy. The combination of RA and MTX is associated with lymphoproliferative disorders (LPD). RA patients with Epstein–Barr virus (EBV) have impaired T‐lymphocyte function, thus allowing an overgrowth of EBV‐positive lymphoblastoid cells. We examined the association of EBV with LPD in immunosuppressed RA patients, particularly those treated with MTX. Aim: To review the relationship between RA, EBV‐associated LPD and MTX use. Methods: We reported two cases of RA patients with long‐term MTX treatment who subsequently developed EBV‐positive LPD, followed by a review of the relevant literature. Results: Compared with normal population, RA patients have a higher risk of lymphoma, with diffuse large B‐cell lymphoma being the most common subtype. MTX withdrawal can lead to lymphoma regression. Other biological therapies, such as abatacept and tocilizumab, are not associated with increased EBV‐positive lymphoma diagnosis in RA patients. Conclusion: The association between EBV, lymphoma and MTX highlights the need to consider reducing or stopping MTX in patients who have had stable RA for many years.